Discovery of BAZ1A bromodomain inhibitors with the aid of virtual screening and activity evaluation. (1st February 2021) - Yang, Zhenyu; Zhou, Yangli; Zhong, Lei
Graphical abstract: Highlights: This is the first discovery report of BAZ1A bromodomain inhibitors. Cpd-2 showed a KD value of 0.52 μM against BAZ1A bromodomain in the microscale thermophoresis (MST) assay. Cpd-2 could be a potential lead compound for subsequent drug discovery targeting BAZ1A bromodomain. Abstract: BAZ1A is a bromodomain-containing protein, and has been recognized as a potential target for multiple diseases, particularly cancer. However, there is no BAZ1A inhibitor reported so far. In this study, we used a consensus docking/scoring strategy to screen for BAZ1A bromodomain inhibitors from commercial chemical libraries and an in-house chemical database. The retrieved hit compounds were evaluated experimentally and four compounds were found to be active against BAZ1A bromodomain. To the most active compounds, similarity and substructure searches were used to find more BAZ1A bromodomain inhibitors. Among all the obtained active compounds, Cpd-2 is the most potent one, which showed a KD value of 0.52 μM. The interaction model of Cpd-2 with BAZ1A bromodomain was revealed by molecular docking. In a cellular assay, Cpd-2 displayed good anti-viability activity against cancer cell lines expressing a high level of BAZ1A. Overall, we discovered a number of BAZ1A bromodomain inhibitors for the first time, which can be a good starting point for subsequent drug discovery targeting BAZ1A bromodomain.